Numerical modelling of waves interacting with the breakwaters of Leixões harbour, Portugal - Maria Graça Neves (2011)
Two numerical models - AMAZON, based on the non-linear shallow-water (NLSW) equations, and IH-2VOF, based on the Reynolds averaged Navier - Stokes (RANS) equations - are planned to be used to model the hydrodynamic processes around the Leixões harbour breakwaters (the existing and the submerged breakwater). In particular, the velocity field between the two breakwaters and the wave overtopping over the existing breakwater will be analyzed. This paper presents the methodology that has been used to analyze the sensitivity of the IH-2VOF results to the porous media parameters that should be calibrated. First results obtained in this study are also presented in order to illustrate this methodology.